Spatial variations of the concentration of heavy metals (Cd, Pb) in the Crassostrea gigas oyster from Lake Nokoué in southern Benin - DASSI, Etiennette; YOUSSAO ABDOU KARIM, ALASSANE; ELEGBEDE MANOU, BERNADIN; ABDOULAYE, DJAFAROU; AGOSSOU, GILDAS FIACRE; ZOFFOUN, Sylvain G. T.; Aina, Martin Pepin; MAMA, DAOUDA (My University, 2022)
Lake Nokoué is located between parallels 6°20' and 6°30' North and meridians 2°20' and 2°35' East. This ecosystem is subject to a strong anthropogenic influence due to direct discharges and polluting inputs of urban and industrial origin drained by rainwater and sea currents. This study consisted of collecting oyster samples from three sites in Lake Nokoué and determining the Cd and Pb levels. The pH, salinity, dissolved oxygen, conductivity and temperature of the water were was also measured at the three stations using a portable HANNA HI 9829 type device to assess the state of the quality of the environment of these organisms. Oyster samples were mineralized and extracted using citrate buffer and a chloroform + dithiver mixture in a 500 mL ampule and measured using a Photolab brand molecular absorption spectrophotometer 6600 UV-VIS. The results show that the waters of Lake Nokoué is influenced not only by marine currents via the Cotonou Channel, but also by continental inputs from the Ouémé River and the Sô River and that the physicochemical conditions are favorable to the development of aquatic organisms. The maximum values of Cd and Pb recorded are respectively 10.40 mg/kg DM (Djidjè site) and 9.39 mg/ kg DM (Agbato site) greatly exceeding the reference values of the French standard set by decree of May 21, 1999 and Regulation (EC) No. 1881/2006. The sanitary quality of the aquatic species of Lake Nokoué in general and that of the oysters in particular must be rigorously monitored because they are highly appreciated by the populations.
Keywords: Contamination; heavy metals; physicochemical quality; oysters; Lake Nokoué